A genre analysis of Islamic academic research article introductions - Ahamad Shah, Mohamed Ismail (s.n, 2013)
In the academic communities, research article serves to disseminate new knowledge and contribute to the academic or professional success of the writer. However, many students or novice writers are unaware of the important aspect of rhetorical organization in the research article writing. The lack of generic knowledge and skills can create difficulty for them in research article writing, particularly in the introduction section. This difficulty also occurs in the writing of Islamic academic research article (RA) introductions. This study explores rhetorical organization of Islamic RA introductions based on swales (1990) CARS (Create a Research Space) model. It aims to identify whether the Islamic RA introductions. Based on the CARS model, sixty Islamic RA introductions were analyzed in terms of the move structure and linguistic features that signal the use of the move